MONITORING MOVEMENT AT MAKLI - R. Eppich; K. A. Mahessar; S. Nawaz (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Monitoring the movement of historic structures on unstable geology is a critical part of conservation. Such documentation can be accomplished using a variety of techniques from close observation to highly accurate instrumentation. However, the monitoring of nearly a hundred structures with varying levels of significance over a large area with limited resources is challenging. This paper describes the approach, methodology, planning, and execution of the initial monitoring system for the historic mausoleums at Makli Hills, Thatta in Sindh (Pakistan). This World Heritage property, located along six kilometers of bluffs above an ancient branch of the Indus River contains the tombs of rulers, poets, and spiritual leaders spanning from the XIVth to XVIIIth centuries. These tombs, built at the edge of eroding bluff, have been subjected to differential settlement leading to a number of past structural failures, serious cracks, deformations, and potential failures. The paper describes this important site, it´s problems, and a methodology to balance the significance and the sheer number of monuments with risk and available budget.